Ruang Ketiga dan Konstruksi Identitas: Hibriditas dalam Karya Mahmoud Darwish - Muhammad Luthfi Zuhdi (Center of Language and Cultural Studies, 2021)
This paper discusses how identity was constructed in Mahmoud Darwish's literary works. Mahmoud Darwish is a symbol of Palestine both poetically and politically. Darwish's life as a refugee and exile greatly influenced his works and attitude towards Israeli-Palestinian peace. This research is qualitative research using literary methods. The data in this study were taken from Mahmoud Darwish’s literary works such as Awraq al-Zaytun (Leaves of Olives), Yawmiyyat Jurh Filastini (Diary of a Palestinian Wound), Muhawalah Raqm 7 (Attempt Number 7), Kazahri al-Lawz aw Ab’ad (Like Almond Flower and Further), Shai’on ‘an al-Wathan (Something about the Homeland) and Dhakirah li-al-Nisyan (Memory for Forgetfulness). In this study, Mahmoud Darwish's works were analyzed using Homi K. Bhabha's post-colonialism theory. Bhabha's idea of hybridity and the third space was used to explain how the homeland was conceived, and identity was constructed in Darwish’s works. The results of this study indicate that the homeland for Darwish is a symbolic and effective one. It can be imagined, but cannot be possessed. Darwish identity was constructed in the third space; a hybrid place where the colonizer and the colonized coexist in the same space.